2017
DOI: 10.3389/fnmol.2017.00103
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Induced Neuroadaptation Is Orchestrated by the Histone Acetyltransferase CBP

Abstract: Homeostatic neural adaptations to alcohol underlie the production of alcohol tolerance and the associated symptoms of withdrawal. These adaptations have been shown to persist for relatively long periods of time and are believed to be of central importance in promoting the addictive state. In Drosophila, a single exposure to alcohol results in long-lasting alcohol tolerance and symptoms of withdrawal following alcohol clearance. These persistent adaptations involve mechanisms such as long-lasting changes in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Both CREBBP and EP300 appear in our top 20 genes related to human alcohol problems and epigenetics (Table 1 ), strongly supporting our interest in cpb-1 . CBP homologs have well described roles in the nervous system response to alcohol in animal models [ 27 31 ], and CREBBP is associated with addiction in humans [ 32 ]. We reasoned that if SWI/SNF is regulating ethanol response behaviors in part through its regulation of cbp-1 , then disrupting function of cbp-1 itself should alter ethanol response behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Both CREBBP and EP300 appear in our top 20 genes related to human alcohol problems and epigenetics (Table 1 ), strongly supporting our interest in cpb-1 . CBP homologs have well described roles in the nervous system response to alcohol in animal models [ 27 31 ], and CREBBP is associated with addiction in humans [ 32 ]. We reasoned that if SWI/SNF is regulating ethanol response behaviors in part through its regulation of cbp-1 , then disrupting function of cbp-1 itself should alter ethanol response behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…In the past 2 years, 3 alcohol studies from different Drosophila groups have identified a set of histone-modifying enzymes with direct roles in controlling adaptive alcohol responses. 60 62 These findings, reviewed below, have strengthened the link between epigenetic modifications and alcohol-induced neuroadaptations and have solidified the importance of the Drosophila model in elucidating the mechanisms of alcohol addiction.…”
Section: Drosophila Paves the Waymentioning
confidence: 90%
“…76 In Drosophila, CBP is encoded by the gene nej and it was recently linked to the development of functional alcohol tolerance. 61,77 In this article, Ghezzi and colleagues first showed that a mutation in nej significantly reduces tolerance to alcohol sedation. Moreover, when nej was artificially induced using a heat-inducible transgene, the experimenters were able to induce an increase in alcohol resistance that resembled the wild-type tolerance phenotype.…”
Section: The Histone Acetyltransferase Creb-binding Proteinmentioning
confidence: 99%
“…Tests of similar learning and memory genes revealed additional notable alcohol phenotypes caused by manipulations of rutabaga (rut) [11,142,197,198], encoding fly adenylyl cyclase, and dnc [193,199,200]. Separate from these pathways and studies, other studies have suggested alcohol-related roles of other genes in the network, including the cAMP-dependent protein kinase A (PKA) [114,197,201], protein kinase C (PKC) [79,[202][203][204], CREB [205][206][207], and CREB binding protein (CBP) [117,208], consistently suggesting a causal role of cAMP signaling pathways in alcohol abuse. The K + channel KCNQ is another example of the one-gene-at-a-time approach and the phenomenon of fly and human studies autonomously arriving at corroborating conclusions.…”
Section: Behavioral Screens In Drosophilamentioning
confidence: 99%